Mechanisms with Negative Stiffnesses for Simplified Designs of Broad Band Passive Vibration Isolation - Feng, Z.C. (Journal of Vibration Testing and System Dynamics, 2026)
Structures with nonlinear stiffnesses have been proposed for passive vibration isolation to achieve high static stiffness and low dynamic stiffness. Unfortunately, the design of nonlinear structures is very cumbersome because of the nonlinear geometry. Mechanisms with negative stiffnesses have found successful applications in industry. These mechanisms could be included in mechanical vibration courses since the design requires only the linear analysis. However, the stiffnesses of these structures with a compressive load are not available in the literature. This paper provides derivation of the stiffnesses of beam mechanisms with compressive loads. The derivation is based on the solution of the ordinary differential equation in the buckling analysis of columns.